Squamous Cell Carcinoma Ex Pleomorphic Adenoma of the Parotid Gland A Case Report with Clinicopathological Review (Journal of Medicine, 2015)
Pleomorphic adenoma, though essentially benign can undergo malignant transformation. This is the case report of a 72 year old male with a giant tumor of parotid gland measuring 20.0X18.0X16.5cm & weighing 7 kg. Pleomorphic adenoma can rarely transform into carcinoma ex pleomorphic adenoma over time as it enlarges; moreover, histologically, squamous cell carcinoma (SCC) is exceedingly rare. Patient developed the tumor for a period over 20 years & it caused withdrawal from social contact. The tumor gradually enlarged without any pain or other complication except for rapid growth & pain a year before. Postoperative facial function and local control of tumor was achieved. Despite Of having a cancer with significant extracapsular invasion, our patient did not present any metastatic focus. Besides morphological patterns, authors need to categorize invasive carcinoma ex pleomorphic adenoma according to its potentiality to metastasize. Various parameters which can predict malignant transformation in pleomorphic adenoma is also yet to be explored.J MEDICINE July 2015; 16 (2) : 118-121